2016
DOI: 10.1093/neuonc/now045
|View full text |Cite
|
Sign up to set email alerts
|

Large-scale assessment of the gliomasphere model system

Abstract: This comprehensive assessment reveals advantages and limitations of using gliomaspheres to model GBM biology, and provides a novel strategy for selecting genes for future study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
78
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1
1

Relationship

4
4

Authors

Journals

citations
Cited by 88 publications
(86 citation statements)
references
References 33 publications
3
78
0
Order By: Relevance
“…But that study has used a small sample size to assess the possible association between the neurosphere formation and clinical outcome of the tumor. A recent study on the relationship between gene expressions based on The Cancer Genome Atlas (TCGA) classification and gliomaspheres has shown that gliomasphere system retains the important expression profiles and molecular pathways, thus can be used to study the important genes associated with glioma malignancy (12). One of the aims of our study was to determine whether GSCs can be isolated and grown from both LGG and HGG, especially low grade, as there were no extensive studies that focused on such population in LGGs (18).…”
Section: Discussionmentioning
confidence: 99%
“…But that study has used a small sample size to assess the possible association between the neurosphere formation and clinical outcome of the tumor. A recent study on the relationship between gene expressions based on The Cancer Genome Atlas (TCGA) classification and gliomaspheres has shown that gliomasphere system retains the important expression profiles and molecular pathways, thus can be used to study the important genes associated with glioma malignancy (12). One of the aims of our study was to determine whether GSCs can be isolated and grown from both LGG and HGG, especially low grade, as there were no extensive studies that focused on such population in LGGs (18).…”
Section: Discussionmentioning
confidence: 99%
“…TCGA classification, EGFR amplification, EGFR v3 status, and doubling time (proliferation rate) were determined as previously described (Laks, et al, 2016)(29). …”
Section: Methodsmentioning
confidence: 99%
“…Primary human glioma cell lines were established at UCLA as described (Hemmati et al, PNAS 2003 (7); Characteristics of specific gliomasphere lines can be found in Laks et al, Neuro-Oncology 2016 (13)). The GL261 murine glioma cell line was a kind gift of Dr. William H. McBride (Department of Radiation Oncology at UCLA).…”
Section: Cell Culturementioning
confidence: 99%